EFFECT OF DAMPER CONFIGURATION ON O-RING QUALITY CHARACTERISTICS DURING POST CURE PROCESS - Arvita Emarilis Intani (POLITEKNIK LP3I JAKARTA, 2026)
Uniform heat distribution during the post cure process is essential for maintaining the dimensional stability and mechanical properties of automotive rubber products. The damper configuration in a post cure oven influences air circulation, which may affect the quality of cured O-rings. This study aimed to compare the effects of Half-Open and Full-Open damper configurations on O-ring quality characteristics, including Inner Diameter (ID), Thickness, and Hardness. An experimental comparative design was employed using 60 O-ring specimens, consisting of 30 specimens for each damper configuration. Product characteristics were measured using a digital vernier caliper, dial thickness gauge, and Shore A durometer. The collected data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene's test, independent sample t-test, and process capability analysis (Cp and Cpk). The results showed that both damper configurations produced O-rings within the specified quality limits. Independent sample t-tests revealed no statistically significant differences in Inner Diameter (p = 0.116), Thickness (p = 0.195), or Hardness (p = 0.147). However, the Half-Open configuration exhibited lower process variation and higher Cp and Cpk values, indicating superior process consistency compared with the Full-Open configuration. These findings suggest that the Half-Open damper configuration is preferable for improving process stability and maintaining consistent product quality during the post cure process in automotive rubber manufacturing.